COVID-19 incidence and cardiorespiratory fitness among first-year college students - Alvaro, Catherine E.; Levers, Kyle S.; Barberio, Matthew D.; Jin, Yichen; Stranieri, Andrew M.; Sacheck, Jennifer M. (Frontiers in Public Health, 2024)
Objective With the emergence of the COVID-19 virus, there was a widespread infection rate among college campuses, creating a need to understand the impact of COVID-19 infection on the health and wellbeing of adolescents. The aim of this study was to examine COVID-19 incidence and cardiorespiratory fitness (CRF) among undergraduate students in the 2 years post-COVID-19 pandemic lock-down. Participants Participants (n = 151) included undergraduate college freshmen students during the 2021–2022 and 2022–2023 academic years. Methods A series of annual surveys (n = 151) and laboratory measures among a sub-sample of participants (n = 28) were conducted to assess COVID-19 incidence, CRF, anthropometrics, and physical activity (PA). Results Over half of participants self-reported COVID-19 infection (59%), “good” or better CRF, a healthy body mass index (BMI), and 25% met PA recommendations. Nearly a quarter, (24%) perceived a negative impact of COVID-19 on their CRF and although not statistically significant, participants who contracted COVID-19 had 46% lower odds of having a positive perception of CRF than those who did not contract COVID-19 before. However, students who were more physically active were more likely to perceive a negative impact of COVID-19 incidence on their CRF (p = 0.035). Conclusion Although no relationship was detected between COVID-19 and CRF, those who perceived a negative impact of COVID-19 on their CRF reported engaging in more physical activity.